(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English Soybean consumption has grown rapidly, but its production increased at a much lower rate, and as a result its demand can only be met by import. On the other hand, the irrigated land most suitable for soybean development is still in a large potential. To utilize the resource, the government made a special effort through intensification and area expansion program as well. The irrigated lowland at West Java northern coastal region is one of strategic opportunities to boost soybean production based on location, accessibility and land suitability. Soybean is usually produced in the second dry season (July-September), and it is expected to increase farm income, to create rural employment opportunity especially for landless farmer. Some influencing factors for further development are among others good seed availability, irrigation and competition of labor used. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Pertumbuhan konsumsi kedelai dari tahun ke tahun terus mengalami peningkatan, sehingga mengakibatkan ketidakseimbangan pertumbuhan konsumsi dan produksi kedelai dalam negeri. Untuk menutupi kekurangan konsumsi dalam negeri terpaksa dilakukan impor. Di lain pihak potensi lahan yang cocok untuk pengembangan kedelai ini masih cukup besar. Untuk memanfaatkan potensi sumberdaya lahan ini pemerintah berusaha melalui berbagai upaya khusus baik melalui intensifikasi maupun ekstensifikasi. Sawah irigasi teknis di Pantura Jawa Barat merupakan salahsatu peluang pengembangan kedelai yang sangat strategis bila dilihat dari letak, aksessibilitas dan kesesuaian bio-fisik lahan. Pengembangan kedelai di lahan ini pada MK II (Juli - September) disamping dapat meningkatkan penerimaan usahatani juga membuka peluang kesempatan kerja bagi buruhtani di pedesaan. Untuk pengembangan selanjutnya faktor yang perlu diperhatikan untuk menunjang keberhasilan program ini antara lain kelembagaan penyediaan benih bermutu, pengaturan air serta persaingan penggunaan tenaga kerja.